Analysis of swimming pool solar heating using the utilizability method - R. S. Gonçalves; Ana I. Palmero-Marrero; Armando C. Oliveira (Energy Reports, 2020)
A study was carried out to predict the long-term energy performance of swimming pool solar heating systems for four Brazilian cities using the utilizability method. The chosen cities were Brasília, Fortaleza, Porto Alegre and S\~ao Luís. The pool area was kept constant and both glazed and unglazed solar thermal collectors were considered for the different locations, with a slope equal to the latitude of each city. The meteorological data used in the analysis such as wind speed, ambient temperature, radiation on a horizontal surface and clearness index were specific for each city and obtained from Meteonorm. The geometric parameters of the collectors were constant for all simulations and the results were carried out with a specially developed computational code. In addition, statistical analyses of the data using ANOVA (Analysis of Variance) and Tukey's test were made.
Keywords: 330; Solar fraction; Swimming pool heating; Utilizability